2019
DOI: 10.5455/javar.2019.f312
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors associated with bovine herpesvirus 1 in Northeast of Algiers

Abstract: Objective: The present study was conducted to estimate the seroprevalence and associated risk factors of bovine herpesvirus 1 (BoHV-1) in a dairy herd in the northeast of Algiers, Algeria. Materials and methods: The target area is in the northeast of Algiers with humid to semi-dry climate and known for its economically important production of cattle. A total of 1,066 randomly selected individual blood samples of dairy herd collected at 120 dairy farms from rural distric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
1
1
Order By: Relevance
“…Increased age has been considered a risk factor for higher prevalence as a result of greater chances of virus exposure to susceptible animals with age. For example, one study noted that BoHV-1 is more prevalent in animals greater than 4 years (Kaddour et al, 2019). However, in the present study age was not found a statistically significant risk for BoHV-1.…”
Section: Discussioncontrasting
confidence: 84%
“…Increased age has been considered a risk factor for higher prevalence as a result of greater chances of virus exposure to susceptible animals with age. For example, one study noted that BoHV-1 is more prevalent in animals greater than 4 years (Kaddour et al, 2019). However, in the present study age was not found a statistically significant risk for BoHV-1.…”
Section: Discussioncontrasting
confidence: 84%
“…Dairy farms should immunize their cattle against common infections such as BVD, IBR, Bovine Respiratory Syncytial Virus (BRSV), Parainfluenza-3 (PI3), clostridial infections, and leptospirosis to prevent or control disease outbreaks. However, several studies (Derdour et al 2017;Kaddour et al 2019) have found that BVD and IBR are present in Algerian dairy herds, even though none of the farmers vaccinated their herds against any of these common infectious agents, excluding rabies and foot and mouth disease. The vaccination program needs to take into account the infectious disease problems in the region as well as other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of BHV-1 infection can be made by direct methods (virus isolation and identification) using PCR, hybridisation and nucleic acid sequencing, and by indirect methods (detection of antibodies against BHV-1) using the ELISA technique and the serum neutralisation test. The disease has been reported in Algeria in cattle through studies conducted on seroprevalence using ELISA, such as those of Kaddour et al (2019) and Derrar et al (2019) where the individual seroprevalence reported was 14.16% and 31.17%, respectively. Herd seroprevalence varied from 50% to 58.33% (Dechicha et al, 2010, Kaddour et al, 2019.…”
Section: Introductionmentioning
confidence: 93%
“…The disease has been reported in Algeria in cattle through studies conducted on seroprevalence using ELISA, such as those of Kaddour et al (2019) and Derrar et al (2019) where the individual seroprevalence reported was 14.16% and 31.17%, respectively. Herd seroprevalence varied from 50% to 58.33% (Dechicha et al, 2010, Kaddour et al, 2019.…”
Section: Introductionmentioning
confidence: 93%